Corn Pest Population Dynamics in Organic Systems Following Soybean: A Three-Year Study - Ioana Grozea; Ana Maria Virteiu; Adrian Grozea; Diana Purice (Universitas Sebelas Maret, 2025)
This study investigated the dynamics of corn pest populations in organic and conventional cropping systems over a three-year corn–soybean–corn rotation (2022 to 2024), conducted in Bihor County, Romania. The experiment was carried out on two farms with similar pedoclimatic conditions (cambic chernozem, pH 6.9, 775 mm annual rainfall), where corn hybrids were grown under identical agronomic conditions, with three replicate plots per treatment. Adult populations of both specific (Rhopalosiphum padi, Ostrinia nubilalis, Helicoverpa armigera, Diabrotica virgifera) and non-specific pests (Phyllotreta atra, Macrosteles spp., Agriotes spp.) were monitored using standardized trap-based sampling. The objectives are to quantify pest pressure across systems and crops and evaluate the influence of soybean as a preceding crop on pest persistence in corn. For corn in 2022, specific pest abundance averaged 1,825.75±131.36 in organic plots vs. 625.25±45.42 in conventional ones (F = 212.84, p < 0.001, Cohen’s d = 11.91). Non-specific pests reached 1,501.33±126.54 in organic corn vs. 834.33±47.60 in conventional (F = 73.02, p = 0.001). In 2024, total pest pressure in organic corn rose to 5,279.67±512.06, compared to 1,683.33±42.22 (F = 146.98, p < 0.001). Pest levels decreased moderately across the organic rotation, suggesting a partial suppressive effect of soybean, absent in conventional plots. Relative abundance of key species exceeded 25 to 30%, indicating a high risk of damage in the absence of intervention. These results have practical implications for integrated pest management (IPM): organic systems require enhanced monitoring and biological control strategies, while soybean’s role in pest carryover should inform rotation planning.